Studi Kepuasan Pelanggan Peserta Jaminan Kesehatan Pada RSUD Arifin Achmad Pekanbaru - Suroto, Bambang (Komunitas Manajemen Kompetitif, 2015)
Abstract: Customers district general hospitals Arifin Achmad particular patient complains always guarantee the services provided. Based on the results of research conducted qualitatively generate customer satisfaction guarantee on Arifin Achmad still not satisfied with the services provided by the hospital. This is because doctors are slow in providing services and in fact I had three days in treated but once a new doctor examined me, but it is handled by the nurse and the absence of good communication in the services provided so that resentment in the liver that can be felt. Then the nurse sometimes less friendly in providing services and being rude to patients while also attending physician to the patient is less communicative and arrogant. guarantees provided by the hospital to patients is low and not maximal, and also evidence of services provided on the basis of existing physical evidence, but in non-physical as officers treatment to patients is low and needs to get attention. Therefore, in order to improve patient satisfaction guarantee and also government officials in this field is the medical and non-medical personnel need to make fundamental improvements in attitudes and behavior, because customer satisfaction is very subjective judgment subjectively that need improvement and also in the form of emotional officer provide services with full attention. Keywords: Customer Satisfaction, Patient Security